Recent urban expansion in the district of La Matanza. The case of private neighborhoods of Bolivian community in the peri-urban area (Huellas, 2025)
Latin American metropolis have experienced deep socio-territorial transformations in recent decades as a result of their expansion. Within the commercial logic framework that implies different forms of residential land use on agglomerations, private neighborhoods were configured as a paradigmatic result of this typical growth in capitalist urbanism. Private urbanizations in the Buenos Aires Metropolitan Region have been widely studied. This work aims at providing a specific contribution by addressing a recent phenomenon of incipient development of private neighborhoods promoted by the Bolivian community, more precisely in the peri-urban area of La Matanza district. The objective is to carry out a first analysis of these projects, their promotion and development from a perspective that considers the spatial and socio-cultural dimensions involved in these proposals. The methodological strategy is qualitative and it is based on surveying social networks advertisements and conducting interviews with real estate developers. Through three analytical axes, breaks and continuities are shown in these neighborhoods with respect to traditional ones. Furthermore, they are framed in the context of generational change in the Bolivian community. Finally, tensions generated in local representations are pointed out.
Keywords: private urbanizations; Bolivian migration; La Matanza